A DFT study on the mechanism of palladium-catalysed tandem reaction of ortho-electron-deficient alkynyl-substituted aryl aldehydes with indoles - Zhao, Ying-Xue; Zhao, Zeng-Xia; Zhang, Hong-Xing (Molecular physics, 2020)
A density functional theory study was carried out to understand the mechanisms of Pd(OAc) 2 -catalysed cyclisation reaction of ortho-electron-deficient alkynyl-substituted aryl aldehydes with nucleophilic attack of indoles leading to the formation indole-substituted indanones in detail. The energy profiles are related to the catalytic cycle, involving alkynyl coordination, 5-exo-dig cyclisation, nucleophilic attack, concerted metalation-deprotonation (CMD), HOAc release, HOAc assisted ring-opening step, and finally alkene insertion to ring rearrangement. Pd(II) coordination with alkynyl and Pd(II) coordination of O of the aldehyde group are latent competitive reaction pathways. The process of indole nucleophilic attack was researched to understand how the alkene interacts with the Pd(II) to facilitate the reactions. When electron-withdrawing group was employed, it plays a key role in controlling the ring size of cyclisation.